CONSUMER WILLINGNESS IN ONLINE BUYING AND SELLING TRANSACTIONS IN MAKASSAR CITY (Fiqhi Muamalah Analysis) - Alimuddin Akib; Muslimin Muslimin; Muammar Bakri; Amiruddin K (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
The development of information technology has driven changes in economic transaction patterns from conventional systems to digital systems through various online buying and selling platforms. This transformation provides convenience in transactions, but also raises various issues related to consumer willingness, information transparency, and the application of business ethics from the perspective of Islamic jurisprudence (fiqhi muamalah). This study aims to analyze consumer willingness in online buying and selling transactions in Makassar City based on the principles of Islamic jurisprudence (fiqhi muamalah). The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, documentation, and literature studies of consumers conducting online transactions. The results show that online buying and selling contracts have fulfilled the pillars and requirements of buying and selling according to Islamic jurisprudence (fiqhi muamalah), namely the presence of a seller and a buyer, the object of the transaction, the price, and the ijab qabul (consent) conducted through electronic media. In addition, transactions are carried out based on the principles of Islamic business ethics, which include honesty (as-sidq), trust, openness (at-tabliqh), justice, responsibility, and benefit, to encourage the formation of consumer willingness. The concept of willingness in online transactions also includes aspects of sharia permissibility, achievement of maqāṣid al-syarī'ah, and the use of qiyas in responding to developments in modern trade technology. Thus, online buying and selling practices in Makassar City are essentially in line with the principles of Islamic jurisprudence (fiqhi muamalah) as long as they are carried out honestly, transparently, fairly, and without elements of usury, gharar, or coercion.